Organizational use of social media during a global health crisis - Shi, Wanzhu; Yeung, Tina; Dmello, Jared (Frontiers in Communication, 2024)
The COVID-19 pandemic initiated new and unprecedented challenges that required organizations to curate timely, accurate and engaging public health information to communicate to local communities during a health crisis. Guided by the social media typology, content analysis was used to analyze tweets from six organizations located in a predominantly Hispanic community responsible for managing the pandemic. Findings revealed that these organizations have actively used Twitter (now known as “X”) to inform local residents about COVID-19 at the beginning of the pandemic and guided them how to respond to this health crisis by providing content with health-related actions. The analysis indicated that redundant digital content without using the local language of the community did not help public health officials communicate effectively to their citizens, thereby increasing their level of engagement and eliciting behavior changes. We suggest that public organizations, government, and healthcare organizations within a minority community need adopt social media strategies that incorporate the local community's language in content generation to foster ongoing conversations, mobilize actions, and elicit behavioral changes within their local communities.